The Great Devonian Controversy : the Shaping of Scientific Knowledge among Gentlemanly Specialists. - Rudwick, Martin J. S. (Science and its conceptual foundations., 1985)
"Arguably the best work to date in the history of geology."--David R. Oldroyd, Science. "After a superficial first glance, most readers of good will and broad knowledge might dismiss [this book] as being too much about too little. They would be making one of the biggest mistakes in their intellectual lives. ... [It] could become one of our century's key documents in understanding science and its history."--Stephen Jay Gould, New York Review of Books. "Surely one of the most important studies in the history of science of recent years, and arguably the best work to date.